2017
DOI: 10.1007/s12311-017-0865-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Gray Matter Alterations in Huntington Disease: A Voxel-Based Morphometry Study

Abstract: Neuropathological and neuroimaging studies in Huntington disease (HD) have suggested a role for the cerebellum. Our goal was to perform a detailed evaluation of cerebellar morphology. We performed the Unified HD rating scale (UHDRS) and Montreal cognitive assessment (MOCA) in 26 HD patients and 26 healthy controls. We created a two-sample test to analyze cerebellar gray matter (GM) differences between groups and another to correlate GM alterations with UHDRS and MOCA, corrected for age, expanded cytosine-adeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Limitations of the Talairach-Tournoux brain atlas are thus circumvented, enabling more accurate depiction than whole-brain methods offer. Previously conducted functional MRI studies relying on SUIT have successfully identified morphologic changes of cerebellar subregions in several neuropsychiatric diseases (Chen et al, 2018; Cocozza et al, 2017; de Azevedo et al, 2017; Piccinin et al, 2017). In addition, these studies showed that SUIT template preserves more anatomical detail of the cerebellum and allows for better localization of cerebellar findings than the commonly-used whole brain Voxel-based morphometry(VBM) MNI template.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of the Talairach-Tournoux brain atlas are thus circumvented, enabling more accurate depiction than whole-brain methods offer. Previously conducted functional MRI studies relying on SUIT have successfully identified morphologic changes of cerebellar subregions in several neuropsychiatric diseases (Chen et al, 2018; Cocozza et al, 2017; de Azevedo et al, 2017; Piccinin et al, 2017). In addition, these studies showed that SUIT template preserves more anatomical detail of the cerebellum and allows for better localization of cerebellar findings than the commonly-used whole brain Voxel-based morphometry(VBM) MNI template.…”
Section: Introductionmentioning
confidence: 99%
“…Structural and functional abnormalities of the cerebellum are present in numerous developmental and acquired neurological conditions, such as developmental dyslexia, autism spectrum disorders, alcohol‐related brain damage, movement disorders (eg, Friedreich ataxia, Parkinson disease, Huntington disease), dementia (eg, Alzheimer disease [AD], dementia with Lewy bodies, frontotemporal dementia), and psychiatric disorders . The contribution of the cerebellum to motor coordination and motor planning is well known, but many studies have downplayed its involvement in other domains despite the mounting evidence over the past 30 years (eg, language, social cognition, interoception).…”
mentioning
confidence: 99%
“…The scale was used in six neuroimaging studies, 75 , 83 , 85 , 87 , 94 , 95 eight cognitive studies, 74 , 82 , 84 , 88 , 89 , 91 , 93 , 96 and three studies examining other clinical aspects of HD (eg, balance, dysphagia) 80 , 90 , 92 …”
Section: Resultsmentioning
confidence: 99%
“…Neuroimaging studies revealed that MoCA scores present significant correlation with N-acetylaspartate (NAA) and glutamate brain levels 75 and with gray matter density in the cerebellum 83 and subcortical structures 95 …”
Section: Discussionmentioning
confidence: 99%